Isolated copper single sites for high-performance electroreduction of carbon monoxide to multicarbon products - Haihong Bao; Yuan Qiu; Xianyun Peng; Jia-ao Wang; Yuying Mi; Shunzheng Zhao; Xijun Liu; Yifan Liu; Rui Cao; Longchao Zhuo; Junqiang Ren; Jiaqiang Sun; et al. (Nature Communications, 2021)
Electrochemical carbon monoxide reduction is a promising strategy to yield valuable multicarbon products but low selectivities and Faradaic efficiencies are common. Here the authors show single atom copper catalyst supported on MXene with high CO reduction performance and stability.